Perlindungan Hukum terhadap Pangan Lokal dalam Menjalin Kemitraan dengan Toko Modern Kota Palembang - Redi Pirmansyah (Wajah Hukum, 2021)
As a tropical country, Indonesia is rich in biological resources that have the potential to develop a variety of unique and distinctive foods, so that through this food diversity condition, it certainly has the potential for national food security. Food security is a condition for fulfilling household food needs, not only in large enough quantities but must be safe, high quality, nutritious, and diverse, this is stated in the Food Law Number 7 of 1996. The purpose of this study is to determine product protection local food in partnership with modern shops in Palembang City. This type of research is a descriptive analysis with an empirical juridical approach. The main data source of this research is literature study, namely by observing, studying, reading legal materials and decisions and documents related to this research. The results of the study suggest that the Regional Regulation of Palembang City Number 25 of 20011 concerning the Establishment of Shopping Centers and Modern Markets which in this regional regulation obliges every entrepreneur who wants to establish a shopping center and modern market in the city of Palembang must provide space for local products including local food. areas to be sold in shopping centers and modern markets in the city of Palembang with the principle of mutual benefit, clearness, fairness and transparency, provided that they meet the standards set.